An in vitro model for assessing effective scrapie decontamination - Gough, Kevin C.; Baker, C.A.; Maddison, B.C. (Elsevier, 2017)
Scrapie infectivity enters the environment via a multiplicity of routes from infected animals. Environmentally associated scrapie persists on farms when infected animals have been removed and is particularly resistant to disinfection. Infectivity within the farm is not adequately removed by current recommended guidelines for farm decontamination. We describe an in vitro method for modelling decontamination, specifically the removal of scrapie prions from the surface of concrete fomites within buildings that have housed scrapie infected animals. Concrete that had been spiked with low amounts of a diluted scrapie positive brain homogenate was sampled before and after decontamination. Extracts were used to seed a semi-quantitative serial protein misfolding cyclic amplification assay (sPMCA). We demonstrate that methods currently recommended for prion decontamination result in inadequate reduction of prion seeding activity within this in vitro assay. Effective treatment was achieved using repeat dosing of surfaces with 20,000 ppm available chlorine for 4 h.